A web-based educational information system for urban agriculture management as a solution to urban land conversion - Arista, Nor Isnaeni Dwi; Himawan, Rifqi; Pratama, Rizhal Akbar Jaya (Institute for Advanced Science, Social, and Sustainable Future (IASSSF), 2025)
Background: Urban industrial development is directly correlated with population density. Data from BPS (Statistics Indonesia) during 1998-2002 indicates a significant conversion of agricultural land to non-agricultural purposes, approximately ±110,000 hectares annually. This highlights the inevitability of urban infrastructure development. As urban expansion reduces agricultural land, population density and food security needs inversely correlate with current land availability. Methods: This research uses problem identification, literature review, potential analysis, and strategy design methodology to address agricultural challenges in urban settings. Finding: Based on these challenges, we propose the